2011
DOI: 10.1515/1542-6580.2599
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical/Experimental Study of an Upflow Anaerobic Sludge Blanket Reactor Treating Domestic Wastewater

Abstract: This work reports a theoretical and experimental study to evaluate the fluid dynamic of an Upflow Anaerobic Sludge Blanket reactor (UASB), treating domestic wastewater in a pilot scale. Simulations were developed using the Ansys CFX 10.0. For validating the numerical results, an experimental study was conducted by monitoring the total concentration of suspended solids in the effluent and pressure along the reactor. The comparative analysis between the numerical and experimental results of the pressure and slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…As a result, the sludge volumetric fraction changed along the reactor. The volumetric fractions of the involved phases (water, biogas and sludge) were reported in Lima et al [26]. According to these authors, the highest sludge concentrations (validated by the experimental results) are in the inlet region (sludge blanket) and on the sloping walls of the three-phase separator and the gas deflector.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…As a result, the sludge volumetric fraction changed along the reactor. The volumetric fractions of the involved phases (water, biogas and sludge) were reported in Lima et al [26]. According to these authors, the highest sludge concentrations (validated by the experimental results) are in the inlet region (sludge blanket) and on the sloping walls of the three-phase separator and the gas deflector.…”
Section: Resultsmentioning
confidence: 72%
“…Similar behavior can be verified in Figure 14 (z = 1.65 and 1.98 m) and Figure 16 velocities of water, biogas and sludge (Figures 12-17) at the inlet of the phase separator are below the critical threshold specified by the literature for domestic sewage (1.1 m/h), there was sludge in the reactor outlet. This indicates that although the upward velocities of the sewage, mainly at the inlet of the three-phase separator, exert some influence on the sludge present at the reactor outlet, other factors should be considered, such as the inclination and arrangement of phase separating elements, as stressed by van Haandel and Lettinga [20] and verified in the simulations of Lima et al [26]. When comparing the mean values of upward velocities of the continuous and dispersed phases, Figures 12-17, for the reactors configurations with deflector inclinations upwards and downwards, except for the three-phase separator region (Figures 16 and 17b), it is found that mean velocities of biogas were equal to mean velocities of water, indicating biogas drag by water.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Taking into consideration the work of Lima et al (2011), which showed that the flow in a similar UASB reactor could be considered symmetric, as well as the computational costs implicated in simulating a full reactor, it was simulated only half of the reactor (longitudinal section). Aiming to obtain a mesh independent result for the simulations, a mesh independence study was performed.…”
Section: Computational Fluid Dynamics Modelmentioning
confidence: 99%